Parallel activation of prospective motor plans during visually‐guided sequential saccades. (21st January 2017) - Bhutani, Neha; Sengupta, Sonal; Basu, Debaleena; Prabhu, Nikhil G.; Murthy, Aditya
Abstract: Behavioural evidences suggest that sequential saccades to multiple stimuli are planned in parallel. However, it remains unclear whether such parallel programming reflects concurrent processing of goals or whether multiple motor plans coexist, unfolding subsequently during execution. Here we use midway saccades, directed at intermediate locations between two targets, as a probe to address this question in a novel double‐step adaptation task. The task consisted of trials where subjects had to follow the appearance of two targets presented in succession with two sequential saccades. In some trials, the second target predictably jumped to a new location during the second saccade. Initially, the second saccade was aimed at the final target's location before the jump. As subjects adapted to the target jump, saccades were aimed to the second target's new location. We tested whether the spatial distribution of midway saccades could be explained as an interaction between two concurrent saccade goals, each directed at the two target locations, or between the initial motor plan to the first target location and a prospective motor plan directed from the initial to the final target location. A shift in the midway saccades' distribution towards the jumped location of the second target following adaptation indicated that the brain can make use of prospective motor plans to guide sequential eye movements. Furthermore, we observed that the spatiotemporal pattern of endpoints of midway saccades can be well explained by a motor addition model. These results provide strong evidence of parallel activation of prospective motor plans during sequential saccades. Abstract : We combined a sequential saccade task with an adaptation paradigm to selectively manipulate the motor gain of the second saccade to study whether midway saccades, in which saccades are directed in between two targets, involved an interaction between sensory, goal or motor representations. Since the endpoint of elicited midway saccades was dependent on the motor gain of the second saccade we suggest motor addition between the first saccade plan and an evolving future motor plan produces midway saccades. These studies provide insights into how sequential eye movements are planned.